A novel rural microcredit decision model and solving via binary differential evolution algorithm. (2019) - Lin, Jiali; Li, Jiachen; Jiang, Dazhi; Li, Kangshun
Generally, as an economic means of lifting people out of poverty, microcredit has been accepted as an effective method for empowering both individuals and communities. However, risk control is still a core part of the implementation of agriculture-related loans business for microcredit companies. In this paper, a rural microcredit decision model is presented based on maximising the profit while minimising the risk. Then, a binary differential evolution algorithm is applied to solve the decision model. The result shows that the proposed method and model are scientific and easy to operate, which can also provide a referential solution for the decision management in microcredit companies.